Assessing efficacy of energy-based devices in melasma: Q-switched Nd-YAG laser vs. Intense Pulsed Light - Rizwan, Muneeza; Shaheryar, Kiren; Zakir, Saira (Journal of Pakistan Association of Dermatologists, 2019)
Background Melasma is a common problem affecting many young females. Energy based devices are now used to treat melasma but there is fear of post-inflammatory hypo or hyperpigmentation, especially in Asian population. There is need to evaluate efficacy and safety of these devices in our population and find out what suits best in Asian skin. There is no study in the literature to the best of our knowledge which made comparison of Q switched Nd:YAG 1064nm laser and Intense Pulsed Light for treatment of melasma. Â Objective To compare efficacy of Q-switched Nd:YAG 1,064nm laser and Intense Pulsed Light in the treatment of melasma in Asian females. Â Methods A total of 60 patients (30 in each group) were included in this study. Group-A was treated with Q switched Nd:YAG 1064nm laser and group-B was treated with Intense Pulsed Light. 4 sessions 3 weekly were given to patients either of IPL or Q switch laser and efficacy was measured by mMASI score one week after completion of four sessions of treatment. All the collected data was entered and analyzed through SPSS version 21. Â Results Mean age of the patients was 31.4Â±4.4 years (group-A) and 34.2Â±5.4 years (group-B). Mean baseline mMASI score was 7.3Â±3.4 and 6.4Â±2.9 in group A and B, respectively (p=0.335); while post treatment mMASI score was 3.6Â±2.1 in group A and 2.7Â±1.6 in group B (p=0.074). No side effects or long term complications were noted. Treatment was effective in 60% of patients in group A while in 80% patients in group B. Difference between two groups was statistically insignificant (p=0.091). Â Conclusion 1064-nm QS Nd: YAG laser and Intense Pulsed Light both were equally effective (p=0.09) and safe for the treatment of melasma. Â